The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmats.2022.857671
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Diluted Al-Mg Alloys With Columnar-To-Equiaxed Transition

Abstract: The objective of the present research is to study the corrosion susceptibility of two Al-Mg diluted alloys (Al-0.5wt.%Mg and Al-2wt.%Mg) with different grains structures obtained by directional solidification (columnar, equiaxed and columnar-to-equiaxed transition, CET) in 0.5% NaCl solution, at room temperature. The corrosion resistance is analyzed by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques in both longitudinal and transversal sections of the samples. The colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The physical meaning of the elements that constitute the equivalent electrical circuit of Figure 15 is described below: RΩ represents the resistance of the electrolyte, Rp, is the resistance to polarization due to the load resistance and CPE is the associated constant phase element. The use of a CPE to replace a capacitor is due to the need to represent the non-ideal behavior of the surface due to the lack of uniformity caused by roughness, porosity, roughness or other factors [18,19,35,39]. The parameter values obtained from the EIS fit are shown in Table 3.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The physical meaning of the elements that constitute the equivalent electrical circuit of Figure 15 is described below: RΩ represents the resistance of the electrolyte, Rp, is the resistance to polarization due to the load resistance and CPE is the associated constant phase element. The use of a CPE to replace a capacitor is due to the need to represent the non-ideal behavior of the surface due to the lack of uniformity caused by roughness, porosity, roughness or other factors [18,19,35,39]. The parameter values obtained from the EIS fit are shown in Table 3.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…In general, the electrochemical response of the systems will be the result of the combination of the different structures and composition of the alloys. It has been shown that the corrosion behavior of aluminum-based alloys will depend on the nature of the secondary phases, their distribution as a result of the different microstructures, their electrochemical behavior and their interaction with the matrix [12,18,19].…”
Section: Introductionmentioning
confidence: 99%